National Security in Times of Revolution: Costa Rica and the Contra War - Vargas González, Hugo M. (2025)
In the 1980s, Central America suffered the hottest phase of the Cold War. The superpowers took a very active role in supporting regional actors, which translated into a crisis of notable intensity. In general, the predominant view on the intensity of the conflict is framed in ignoring what happened in Costa Rica, privileging the tragedy that occurred in the rest of Central America. However, in that country there were strong manifestations of the crisis of political violence, that go through migrations, the activities of armed groups and espionage, kidnappings and acts of terrorism, as well as attempts to involve the country in a more intense way in the conflict in Nicaragua.